(untitled) (Tunas Geografi, 2021)
The objective of this research is to investigate Housewife resilience for confronting COVID 19. The method used is ethnography because of research related to social community, culture and tradition. Data are collected through in-depth interview with the head of the neighbourhood unit and his housewife, documentation and observation. The sample is selected using a purposive sampling technique. The result is analysed through triangulation which is mixing some gathering data method. The result show that housewife confront to life perturbances because they have multiple tasks including work in the household and instructing kids for learning online. The other finding is housewife create resilience through creating and practising food recipes new. The method for food recipes new is studied by youtube and the internet. The other is to adjust nutrient for a family like they cook vegetable and giving vitamin C for family. The impact is family can achieve resilience because they were healthy family. It can be enhanced by social resilience where the household wife still builds social activity by way of wearing a mask and face shield for protecting self and family. The resilience also is encouraged by social capital like social bridging, the head of the neighbourhood unit as bridge socially among the member of societies to health officer and village officer. The purpose is to obtain updated information about COVID 19. Lastly, mutual visiting among of housewife have created resilience because they contribute money to support another housewife when they suffer from an ailment like COVID 19.